A study of the facilitating and hindering factors in the comprehension and use of information about children and toddlers’ oral health for parents and caregivers - Zanchetta MS, Moreira AV, Galhego-Garcia W (ARCHIVES OF HEALTH INVESTIGATION, 2019)
The research will analyze the social impact of "Sorriso Feliz", an oral health promotion program developed in the city of Birigui, in the state of São Paulo. This program engages dentistry students in educating primary caregivers on the proper oral hygiene practices for children between four months and seven years of age. The research focus is on understanding the participation of primary caregivers, mainly mothers, in this initiative. The design is impact evaluation (Rossi, Lips ey, & Freeman, 2004) using a qualitative descriptive approach (Creswell, 2013). The methods are individual interviews and focus groups with 40 to 70 parents and educators of children who attend local daycare centers (Centros de Educação Infantil). Interviews will be conducted at the daycare centers. The goal is to learn more about what are the main benefits and barriers perceived by them while trying to apply what they have learned through the Sorriso Feliz initiative, in the home. Results will be analyzed qualitatively. The theoretical framework is the Population Health Promotion (PHP) mode l, developed by Health Canada (Hamilton & Bhatti, 1996). This three-dimensional model looks at the interaction between determinants of population health, levels of potential interventions, and major actions for health promotion (Hamilton & Bhatti, 1996). The expected outcome is the understa nding and outlining of factors that support or make it difficult for caregivers to routinely engage children in oral hygiene practices. Preliminary dissemination of findings will be at local level with presentations to professional and lay audiences. Future final dissemination of the results will include, but is not limited to, submission of abstracts for national and international conferences, and production of presentation materials for strategic audiences. This research can potentially inspire further investigations within the subject of oral health promotion strategies aimed at school-aged children, both in Canada and Brazil. This study has been approved by both Ryerson University’s and UNESP’s Ethics Boards. Descriptors: Oral Health; Children; Todler.